The Utilization of YouTube Animated Video Media in Aqidah Akhlak Learning for Grade VIII to Improve Students’ Learning Motivation at MTsN 4 Banda Aceh - Nadhilla Khairuni; Sri Mawaddah; Muhammad Doni; Syahrizal Syahrizal; Hayati Hayati (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
Poor student motivation in Akidah Akhlak topics as a result of traditional, teacher-centered techniques, which resulted in poor involvement, attention, and interest, served as the impetus for this study. Using animated YouTube videos that highlighted the inspirational tale of Prophet Musa, it sought to increase the motivation of eighth-grade pupils at MTsN 4 Banda Aceh. The study was carried out with 27 students in two cycles of planning, action, observation, and reflection using a qualitative Classroom Action Research (CAR) methodology based on Kemmis and McTaggart. Descriptive analysis was used to examine data from observations, questionnaires, interviews, and documentation. The usefulness of animated movies in education was demonstrated by the results, which revealed that motivation went from 62.9% (good) in Cycle I to 96% (very excellent) in Cycle II, showing better attention, involvement, confidence, and knowledge of Prophet Musa's beliefs